2016
DOI: 10.1113/jp272297
|View full text |Cite
|
Sign up to set email alerts
|

Attenuated flow‐induced dilatation of middle cerebral arteries is related to increased vascular oxidative stress in rats on a short‐term high salt diet

Abstract: The aim of this study was to determine flow-induced dilatation (FID) and the role of oxidative stress/antioxidative capacity in isolated, pressurized middle cerebral arteries (MCAs) of high salt (HS)-fed rats. Healthy male Sprague-Dawley rats (11 weeks old) were fed low salt (0.4% NaCl; LS group) or high salt (4% NaCl; HS group) diets for 1 week. Reactivity of MCAs in response to stepwise increases in pressure gradient (Δ10-Δ100 mmHg) was determined in the absence or presence of the superoxide dismutase (SOD) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
70
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(76 citation statements)
references
References 60 publications
6
70
0
Order By: Relevance
“…Activity of enzymes was expressed as U/mg protein (U/mg P) and protein concentration was determined by Bradford protein assay. All measurements were done at Lambda 25 UV-Vis spectrophotometer equipped with UV WinLab 6.0 software package (PerkinElmer For the Better, Waltham, Massachusetts, USA) [29].…”
Section: Western Blot Analysismentioning
confidence: 99%
“…Activity of enzymes was expressed as U/mg protein (U/mg P) and protein concentration was determined by Bradford protein assay. All measurements were done at Lambda 25 UV-Vis spectrophotometer equipped with UV WinLab 6.0 software package (PerkinElmer For the Better, Waltham, Massachusetts, USA) [29].…”
Section: Western Blot Analysismentioning
confidence: 99%
“…ANG II-induced vascular oxidative stress and hypertension are also exacerbated with aging (66,74), and these responses to ANG II were eliminated in aged mice lacking SMC-MRs (74). In addition to ANG II, many other factors, including elevated Na ϩ , can modulate vascular oxidative stress (16,28,39). Overall, the new data support that in male mice, the MR, specifically in SMCs, plays a critical role in driving resistance vessel tone, oxidative stress, and vasoconstriction in the aging vasculature thereby contributing to rising BP with aging (66,74).…”
Section: Mice Lacking Smc-mrs Are Protected From Vascular Agingmentioning
confidence: 99%
“…HS-induced endothelial dysfunction is caused by decreased plasma concentration of ANG II which leads to increased oxidative stress [139,142,143], as demonstrated in SS.BN13 consomic rats studies [139], leading to impaired relaxation of middle cerebral artery (MCA) in response to hypoxia and ACh due to decrease in vascular antioxidative capacity [144]. Importance of ANG II is further supported by intravenous infusion of suppressor dose of ANG II during HS diet which restores normal vascular relaxation and restores ROS concentration to normal values [145].…”
Section: Arachidonic Acid Metabolites and High-salt Dietmentioning
confidence: 99%
“…Studies on Ren1-BN congenic rats showed that a short-term increase in dietary salt intake reduces the expression of the Cu/Zn SOD and Mn SOD in the cerebral vasculature and that ANG II infusion prevents the reduction of Cu/Zn SOD expression, but not Mn SOD expression, in HS-fed animals [143]. Recent studies showed that, except for reduced protein levels of SOD isoforms, HS intake also significantly reduced the level of mRNA expression of glutathione peroxidase 4 GPx4, very important enzyme in maintaining reduced levels of lipid peroxidation and oxidative stress [142]. Treatment with TEMPOL [136,148] (which is a SOD mimetic) returns the NO level to the concentrations similar to the ones in the animals on a normal salt diet which indicates that the O2 -· is responsible for the oxidation of NO under these conditions.…”
Section: Arachidonic Acid Metabolites and High-salt Dietmentioning
confidence: 99%